Animated Video on Thermochemistry Materials with Everyday Life Phenomena to Increase High School Students Understanding - Anggraeni, Dian Ajeng; Kamaludin*, Agus; Safarova, Aytan (Universitas Syiah Kuala, 2024)
The low innovation of learning media used in online learning causes the learning process not to take place optimally. This incident gave rise to the phenomenon of learning loss. This study aims to develop and assess the quality of animated videos that contain everyday life phenomena on thermochemistry material to increase students' understanding of online learning. The method used in this research is research and development with a 4D model (define, design, development, and dissemination). This research used a purposive sampling technique limited to chemistry teachers and high school students in grades XI and XII. The product was validated by material experts, media experts, and four reviewers and was responded to by ten students. The instruments used were validation sheets, product quality assessment sheets, and student responses. The results of the evaluation of the quality of animated videos by material experts were 91.4% with very good criteria, media experts 90% with very good criteria, and reviewers 90.9% with very good criteria. Ten high school class XI students responded positively, with a percentage of 93%. So, it can be concluded that the product developed is suitable for use as an alternative medium in online learning of thermochemical material to increase student understanding